Localization of the Inhibitory Site(s) of Pentosan Polysulphate in Blood Coagulation - Wagenvoord, R; Hendrix, H; Soria, C; Hemker, H C (Thrombosis and Haemostasis, 1988)
We studied the inhibitory effect of pentosan polysulphate (PPS, Hémoclar®) on thrombin formation in blood coagulation. In contrast to a current hypothesis (1) the anti thrombin III independent effect of PPS on blood coagulation is not caused by preventing the binding of the factors IX, IXa, X, Xa, VIII, V, Va and II onto procoagulant phospholipids.We investigated the activation by thrombin of factors I, V and VIII. A strong inhibitory effect of PPS on factor VIII activation could be observed. Inhibition of the activation of factor V to the same extent requires about 30-fold higher concentrations of PPS, whereas the activation (clotting) of fibrinogen is not inhibited. The effect of PPS on factor VIIIa is two-fold: A) it inhibits its formation and B) it inhibits its function probably by the formation of a factor VIIIa-PPS complex.Prothrombinase, constituted of purified factors Xa, Va and phospholipids was not inhibited by PPS, neither were incomplete forms of this enzyme, lacking phospholipids or factor Va. The complete factor X activating enzyme (factors IXa, VIIIa and phospholipids), however, was strongly inhibited, but incomplete forms, lacking factor VIII, were not. The inhibition of the complete enzyme can be explained by reversible binding of PPS to factor VIIIa (causing an inhibition of its function) and it is not an effect on the enzymatic function of the complete enzyme. On saturation of the enzyme with an excess of factor VIIIa no inhibition by PPS is noticed.We postulate therefore that the antithrombin III independent inhibitory effect of PPS on thrombin generation on blood coagulation is by interaction with factor VIIIa. This effect is additional to the heparin-like action of PPS, i.e. potentiation of the activity of antithrombin III and/or heparin cofactor II. At concentrations attained during therapeutic use the action of pentosan polysulphate on factor VIIIa is the only one that will significantly inhibit the coagulation mechanism.
Keywords: Pentosan polysulphate; Blood coagulation